The caretaker days and my story - Rahman, Latifur, 1936- (Dhaka : Mullick Brothers, 2002)
Memoirs of Latifur Rahman, b. 1936, former Chief Justice and Chief Adviser of caretaker government of Bangladesh from July 15, 2001 to October 10, 2001, under which the nation's general elections were organised; includes autobiographical references.
Keywords: Judges -- Bangladesh -- Biography